Comparing Blanket vs. Selective Dry Cow Treatment Approaches for Elimination and Prevention of Intramammary Infections During the Dry Period: A Systematic Review and Meta-Analysis - Kabera, Fidèle; Roy, Jean-Philippe; Afifi, Mohamed; Godden, Sandra; Stryhn, Henrik; Sanchez, Javier; Dufour, Simon (Frontiers in Veterinary Science, 2021)
A systematic review and a series of meta-analyses were conducted to investigate the efficacy of selective dry cow antimicrobial treatment (SDCT) (in which only infected quarters/cows were treated with an antimicrobial) compared with blanket dry cow treatment (BDCT) (all quarters/all cows received an antimicrobial, regardless to their infection status). A full detailed protocol was published before initiating this review. Studies reporting on: 1) proportion of untreated quarters or cows when using SDCT ; 2) intramammary infections (IMI) incidence risk over the dry period; 3) IMI elimination risk; 4) post-calving IMI prevalence; 5) early lactation clinical mastitis incidence; or 6) subsequent lactation milk yield, and somatic cells counts were considered eligible. Thirteen articles representing 12 controlled trials, whether randomized or not, were available for analyses. SDCT reduced the use of antimicrobials at dry-off by 66% (95%CI: 49 – 80). There was no difference in the elimination of existing IMI at dry off, between SDCT and BDCT. Meta-regression showed that risk of acquisition of new IMI during the dry period, IMI risk at calving, early lactation clinical mastitis risk, and early lactation milk yield and somatic cells counts did not differ between SDCT and BDCT as long as an internal teat sealant (65% bismuth subnitrate) was administered to untreated healthy quarters/cows at dry off. For trials not using internal teat sealants, SDCT resulted in higher risk than BDCT of acquiring a new IMI during the dry period and of harboring an IMI at calving. Evidences strongly supports that SDCT would reduce the use of antimicrobials at dry off, without any detrimental effect on udder health or milk production during the first months of the subsequent lactation, if, and only if, internal teat sealants are used for healthy, untreated quarters/cows.